Studi Numerik Steady RANS Aliran Fluida di Dalam Asymmetric Diffuser - Klistafani, Yiyin (Politeknik Negeri Ujung Pandang, 2017)
Research on fluid flow becomes a necessity to develop technology and for the welfare of human beings on earth. One of them is study of fluid flow in the diffuser. The example of diffuser application is used as a flue gas duct in the car or motorcycle. In addition, diffuser is also applied in air conditioning systems. Diffuser is a construction that able to control the behavior of the fluid. The increasing of cross section area in the diffuser will generate a positive pressure gradient or also called adverse pressure gradient (APG). The greater APG that happens, the greater energy required by the fluid to fight it, because APG will lead to separation. This study aimed to evaluate the numerical fluid flow in the asymmetric diffuser with divergence angle (θ) = 10 ° (upper wall) and widening one vertical side (α) of 20 ° (front wall). The Reynolds number is 8.7 x 104 by high inlet diffuser and the maximum velocity at the inlet diffuser. Turbulence models used are standard k-ɛ, realizable k-ε, and shear stress transport (SST) k-ω. Numerical study of steady RANS used Fluent 6.3.26 software. Results of numerical visualizations show that huge vortex established in diffuser, that’s why performance of diffuser is not optimal. In addition the location of separation point shown by SST k-ω is earlier than other turbulence models (standard k-ε and realizable k-ε).